2022
DOI: 10.1127/entomologia/2021/1357
|View full text |Cite
|
Sign up to set email alerts
|

Silicon accumulation in maize negatively impacts the feeding and life history traits of Spodoptera exigua Hübner

Abstract: Silicon (Si) accumulation in plant tissues helps alleviate abiotic and biotic stresses, including infestation by insect pests. Here, we tested the hypothesis that Si concentration in maize leaves negatively impacts Spodoptera exigua Hübner (Lepidoptera: Noctuidae) with respect to: (i) feeding preferences; (ii) leaf digestion; and (iii) life history traits. We produced three groups of maize plants cultivated in a hydroponic system that had contrasting Si concentrations in their tissues (i.e., 0.21 ± 0.03, 4.45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Silicon applications signi cantly decreased the population of immature white ies and tomato leaf miner on tomato crop in the greenhouse; Si-foliar spraying was more effective in reducing the population density of these key pests compared to Si-soil drench application [16]. Similar con rmatory results were obtained by Pereira et al [17] who demonstrated the larval mortality of S. frugiperda on Si supplemented plants. After 48 h of being fed, they observed that larval mortality was about six times higher on plants receiving Si applications than plants with no Si.…”
Section: Discussionsupporting
confidence: 66%
“…Silicon applications signi cantly decreased the population of immature white ies and tomato leaf miner on tomato crop in the greenhouse; Si-foliar spraying was more effective in reducing the population density of these key pests compared to Si-soil drench application [16]. Similar con rmatory results were obtained by Pereira et al [17] who demonstrated the larval mortality of S. frugiperda on Si supplemented plants. After 48 h of being fed, they observed that larval mortality was about six times higher on plants receiving Si applications than plants with no Si.…”
Section: Discussionsupporting
confidence: 66%
“…The life table is an important tool for studying population ecology (Nika et al 2021;Leroy et al 2022), as it provides a clear overview of parameters such as survival rate, development time, longevity and fecundity (Chi et al 2022a;. The impact of cyetpyrafen on the life history traits of P. persimilis is a key aspect of the combined strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Maize plants (Zea mays L. var Delprim) were grown using a hydroponic production system under the same cultivation parameters as those previously described in Leroy et al (2022b). All assays were performed in Gembloux in 2019.…”
Section: Hydroponic Systemmentioning
confidence: 99%